New Multi-step Worm Attack Model - Yusof, R.; Selamat, S. R.; Sahib, S.; Abdollah, M. F.; Mas'ud, M. Z.; Ramly, M. (Journal of Computing, 2010)
The traditional worms such as Blaster, Code Red, Slammer and Sasser, are still infecting vulnerable machines on the internet. They will remain as significant threats due to their fast spreading nature on the internet. Various traditional worms attack pattern has been analyzed from various logs at different OSI layers such as victim logs, attacker logs and IDS alert log. These worms attack pattern can be abstracted to form worms’ attack model which describes the process of worms’ infection. For the purpose of this paper, only Blaster variants were used during the experiment. This paper proposes a multi-step worm attack model which can be extended into research areas in alert correlation and computer forensic investigation.